Efektivitas Program Kampung Keluarga Berencana di Kelurahan Sidotopo Kecamatan Semampir Kota Surabaya - Dhea Eka Anggraeni; Sri Wahyuni; Deasy Arieffiani (Public Administration Dept, Faculty of Social and Political Science, 2022)
The purpose of the study was to analyze the effectiveness of the Family Planning Village Program in Sidotopo Village, Semampir District, Surabaya City. The method used in this study is a qualitative descriptive method. Data collection techniques in this study using observation, interviews, and documentation. The theory in this research is the theory of program effectiveness according to (Siagian, 2008) and also the theory of success of the family planning program according to the BKKBN. The results of this study indicate that the KB Village Program in RW 12, Sidotopo Sub-district, Semampir Sub-district has been effective, with 7 indicators from (Siagian, 2008) & BKKBN there are four effective indicators, namely, High Community Participation for the advancement of KB village, variety of activities implemented in an integrated manner, both government programs and community innovation, Clarity of goals to be achieved with sub-indicators of precise and targeted targets, and Clarity of strategy for achieving goals with sub-indicators of Impact of the Family Planning Program.